A common self-advantage across the implicit and explicit levels for self-body recognition - Xiang, Sijia; Zhao, Minghui; Yu, Lunhao; Liu, Ning (Frontiers in Psychology, 2023)
Although self-bias has been extensively studied and confirmed in various self-related stimuli, it remains controversial whether self-body can induce recognition advantage at the explicit level. After careful examination of previous experiments related to self-body processing, we proposed that participant strategies may influence explicit task outcomes. To test our hypothesis, we designed a novel explicit task. For comparison, we also conducted classic explicit and implicit tasks. With the newly designed explicit task, we found clear and robust evidence of self-hand recognition advantage at the explicit level. Moreover, we found that there was a strong link between self-advantage found in the classic implicit task and the newly designed explicit task, indicating that the self-advantage processing by these two pathways may be linked. These findings provide new insights into the long-standing inconsistencies in previous studies and open a new avenue for studying self-bias using self-body stimuli.